Sunt criteriile de convergenţă incompatibile cu o strategie orientată spre creştere? - Lucian-Liviu Albu (Romanian Journal of European Affairs, 2001)
Considering the prospects of Romania’s intehgration into European Union (EU), the fundamental objctive is the creation of a functioning market economy, compatible with the Union’s norms, mechanisms, institutions and policies. Hence, the convergence that is presently taking shape, should be primarily built on a proficient evaluation of the specific capabilities, as well as of the national and international circumstances. In the case of Romania, there is a double imperative: first, concluding the transition to the market economy and second, a successful preparation of the integration into the EU. This article attempts to asses the theory of incompatibility between the convergence criteria (the so-called Maastricht criteria) and the growth-oriented economic policies, since the real evolution of the national economy looks constrained by the fetters of a “vicious circle” characterized by the deepening of the gaps in productivity and living standard compared with the situation in the EU.